Antioxidative Properties of Red Palm Fat Blended With Celery and Tomato Extracts In MDCM Sausages - A.S. Babji; Y.J. Ee; A.A. Rahim; N. Abdullah (COSTAM and Akademi Sains Malaysia, 2024)
Extracts obtained from celery and tomato were evaluated for the antioxidative effects in delaying lipid oxidation in mechanically deboned chicken meat (MDCM) sausages during child storage (4°C) for 12 days. There were significant differences in the thiobarbituric acid (TBA) values (p<0.05) between the control sample and samples treated with red palm fat plus celery extract and tomato extract respectively. Differences in the peroxide value (PV) between the control sample and the samples treated with red palm fat plus celery and tomato were significant (p<0.05) particularly after -12 days of storage. Sausages blended with red palm fat and tomato extracts showed the lowest TBA and PV throughout storage, indicating synergistic effects of natural carotenoids and tocopherols acting with plant extracts in delaying lipid oxidation effectively. The pH values for all treatments decreased as the storage time increased. There were significant differences (p<0.05) between treatments in total plate count (TPC) from 0-12 days throughout chilled storage.